VERBA RESIPROKAL DALAM BAHASA MINANGKABAU DI KECAMATAN PATAMUAN KABUPATEN PADANG PARIAMAN - Amriwati, Rini; Agustina, Agustina; Ngusman, Ngusman (Universitas Negeri Padang, 2018)
The purpose of study were toÂ describe process of formation of reciprocal verbs and the meaning of reciprocal verbs in Minangkabau language in the Kecamatan Patamuan Kabuapten Padang Pariaman. This research data in the form of words, phrases, and from oral sources in the form of public speech in Kecamatan Patamuan Kabupten Padang Pariaman. The findings of this research are: First, the process of forming a reciprocal verb consists of, (1) the formation pattern of affixation ie, the prefix of the base form (v / n / a), the prefix ba- + the basic form + the suffix -an, the baka- the basic form (v / n / a), the basic shape prefix (n), the basi- morpheme + the basic form (v), and the standard- (basic) base morpheme (v), (2) the reduplication forming pattern, (v) + prefix of maN- + the basic form (v), the basic shape prefix (v / n / a) + suffix -an, and (3) the basic shape reduplication + the suffix -an, and (3) the pattern formation of the composition of the basic form (n) + adjectives. Second, the meaning of the reciprocal verbs is twofold (1) the act states the active activity and (2) the state states the activity is done in a passive way.Â Keywords: process, mean, verbs, reciprocal, Minangkabau language